Salt, light and a city : introducing missional ecclesiology - Hill, Graham (Eugene, Oregon : WIPF & STOCK, 2012)
"Enormous challenges and opportunities face the Christian church in our globalized, rapidly changing world. It is becoming increasingly clear that the church and its leaders need a missional self-understanding. In this volume, Graham Hill asks: "What does it mean for the church to be truly missional?" This book outlines the thought of twelve leading thinkers, and puts their thinking into conversation with a missional understanding of the church. Most of the missional literature of the past twenty years is practical, telling us how to be a missional church, rather than why certain theological themes compel the church toward a missional self-understanding and existence. This book takes a different approach. It outlines a basic missional understanding of the church by engaging theology and Scripture. It examines some of the key theological themes that are foundational for a missional church, and does this in conversation with twelve leading thinkers. This book provides indispensable foundations for a Christ-centered, gospel-shaped, theologically informed, and systematic missional view of the church."--Publisher's description.
The courageous and future church: Being salt, light and a city
Includes bibliographical references
Keywords: Church; Church -- History of doctrines; Mission of the church